Female Cops in Linda Castillo's and Anne Hillerman's Fiction - Kopecká, Kristýna (Univerzita Pardubice, 2024)
This diploma thesis concentrates on female cops as main characters in mystery fiction by American authors Linda Castillo and Anne Hillerman. Through the lens of feminist literary criticism, the analysis of four chosen novels explores the forms of female empowerment in stereotypically male-dominated environment of police force. Since both authors use distinctive environments of the Amish society and the Navajo nation respectively, the analysis focuses on the role the environment plays in either support or subversion of stereotypical gender roles. Gender dynamics within the private and professional domains between the main male and female characters is explored together with the role of sexuality and violence.
Policistky ve fikci Lindy Castillo a Anne Hillerman
Keywords: detektivní román; policejní procedurál; feministická kritika; genderové role; ženy policistky; Castillo, Linda; Hillerman, Anne; crime fiction; police procedural; feminist criticism; gender roles; female cops